Workshop on Making Complementary Foods as an Effort to Prevent Stunting in Sukoraharjo Village, Kedamean District, Gresik Regency - Budhi Setianto; Agus Aan Adriansyah; Abdul Hakim Zakkiy Fasya; Yauwan Tobing Lukiyono; Mery Susantri; Nikmatus Sa'adah (UNUSA Press, 2026)
Stunting is a condition in which a child's body fails to grow due to chronic malnutrition so that the child's life is too short. The prevalence of stunting in toddlers according to the World Health Organization (WHO) is the country with the third highest prevalence in the Southeast Asia/South-East Asia Regional (SEAR), the prevalence of stunting in Indonesia in children under five in 2017 was 36.4% and in 2018 it was 30.8%. One of the prevention of stunting can be provided by providing companion food from 6-24 months. By holding a workshop related to making complementary foods to prevent stunting, this workshop aims to provide insight to the residents of Sidoraharjo about the importance of knowledge in preparing complementary foods, and how to make them, as well as preparing the complementary food process. 87.8% and knowledge increase 16.2%